Analisis Koperasi Berprestasi dan Strategi Pengembangannya di Kota Jambi melalui pendekatan SAWSWOT - Yuvanda, Sesraria; R, Muhammad Rachmad; Rohayani, Hetty; Zulpandi, Zulpandi (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the best-performing cooperatives in Jambi City and their development strategies. This study uses the Simple Additive Weighting (SAW) analysis model and a SWOT analysis model based on SAW. The results show that the best-performing cooperative selected from the respondent cooperatives in Jambi City is the BMT Bina Insan Sejahtera Jambi Cooperative as the first rank. Meanwhile, the second and third ranks are occupied by the Sehati Makmur Abadi Cooperative and the Telanai Branch of Kopkar Amartha. The development strategy is to increase turnover and cooperative business development, the number of members and member savings, and the activeness of cooperative members through cooperative education.